Liver glutathione depletion after preservation and reperfusion in human liver transplantation - Grezzana Filho,Tomaz de Jesus Maria (2006)
PURPOSE: The oxidative stress is an important mechanism responsible for dysfunction after orthotopic liver transplantation (OLT). Glutathione (GSH) low levels after cold storage render the grafts vulnerable to reperfusion injury. Aim of this study was to evaluate GSH and oxidized glutathione (GSSG) liver concentrations, the hepatocellular injury and function in optimal and suboptimal grafts after human OLT. METHODS: Liver biopsies were taken in 33 patients before the implant and two hours after reperfusion, allowing determination of GSH, GSSG and oxidative stress ratio (GSH/GSSG). Serum transaminases, prothrombin activity (PT) and factor V were measured to evaluate injury and function respectively. Histopathological injury was analyzed by an index of five parameters. RESULTS: There was a decrease in GSH (p<0.01) after reperfusion (0.323 ± 0.062 ìmol/g to 0.095 ± 0.01 ìmol/g and 0.371 ± 0.052 ìmol/g to 0.183 ± 0.046 ìmol/g) in suboptimal and optimal groups, respectively. An increase of GSSG (p<0.05) occurred after reperfusion (0.172 ± 0.038 ìmol/g to 0.278 ± 0.077 ìmol/g and 0.229 ± 0.048 ìmol/g to 0.356 ± 0.105 ìmol/g) in suboptimal and optimal groups, respectively. A decrease (p<0.01) occurred in the GSH/GSSG ratio after reperfusion (2.23 ± 0.31 to 0.482 ± 0.042 and 2.47 ± 0.32 to 0.593 ± 0.068) in suboptimal and optimal groups, respectively. Histopathological injury scores were higher (p<0.05) in the suboptimal group than in optimal (6.46 ± 0.4 vs. 5.39 ± 1.1) and showed correlation with PT and factor V in the optimal group (p<0.05). Multivariate analysis pointed steatosis as an independent risk factor to histopathological injury (p<0.05). CONCLUSION: There was a significant GSH depletion and GSSG formation after cold storage and reperfusion due to a similar oxidative stress in optimal and suboptimal grafts, but these levels were not related to graft viability.